2017
DOI: 10.1016/j.joen.2016.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Dental Pulp Tissue Regeneration Using Dental Pulp Stem Cells Isolated and Expanded in Human Serum

Abstract: Dental pulp-derived stem cells (DPSCs) have the potential to regenerate dentin and dental pulp tissue due to their differentiation capacity and angiogenic properties. However, for regenerative approaches to gain regulatory and clinical acceptance, protocols are needed to determine more feasible ways to cultivate DPSCs, namely without the use of xenogeneic derived components (animal sera) and exogenous growth factors. In this study, human DPSCs were isolated from 3rd molars and expanded in standard culture cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 28 publications
1
39
0
4
Order By: Relevance
“…However, to be able to use DPSCs clinically, the cells should be preferably cultivated in a defined medium produced under conditions of current good manufacturing practice (cGMP) (Bakopoulou et al 2017). Previous studies have also shown that human serum was a suitable alternative to FBS for expansion of DPSCs while keeping their angiogenic potential and regenerative capacity (Khanna-Jian et al 2012;Piva et al 2017). Therefore, in the current study, we aimed to investigate the effect of a new cGMP xeno-/serum-free medium (XSF; PRIME-XV® MSC expansion XSFM, Irvine Scientific, USA) on DPSCs in vitro applications prior to future in vivo experiment.…”
Section: Introductionmentioning
confidence: 99%
“…However, to be able to use DPSCs clinically, the cells should be preferably cultivated in a defined medium produced under conditions of current good manufacturing practice (cGMP) (Bakopoulou et al 2017). Previous studies have also shown that human serum was a suitable alternative to FBS for expansion of DPSCs while keeping their angiogenic potential and regenerative capacity (Khanna-Jian et al 2012;Piva et al 2017). Therefore, in the current study, we aimed to investigate the effect of a new cGMP xeno-/serum-free medium (XSF; PRIME-XV® MSC expansion XSFM, Irvine Scientific, USA) on DPSCs in vitro applications prior to future in vivo experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, adult cells have been more frequently studied in regenerative medicine, because they are readily available, in addition to being capable of differentiating into various cell types, such as osteoblasts, chondrocytes, myoblasts, hematopoietic and neural cells, originating bone, cartilage, muscle, vascular and nerve tissue, respectively [6][7][8][9]. These cells may be found in bone marrow, adipose tissue, umbilical cord and in dental tissues [14][15][16]. With reference to dental tissues, various types of adult cells have been isolated from the periodontal ligament, papillae, primary and permanent tooth pulp, and are considered promising alternative for tissue engineering [17][18][19][20][21].…”
Section: Cellsmentioning
confidence: 99%
“…The stem cells found in primary tooth pulp present high potential differentiation into odontoblasts, osteoblasts, adipocytes and chondrocytes [18][19][20][21][22][23]. Those derived from permanent teeth, specifically found in third molar pulp, may differentiate into odontoblasts, adipocytes, chondrocytes and myoblasts [15,24,25]. Both primary and permanent tooth sources of stem cells may be used for endodontic and bone regeneration.…”
Section: Cellsmentioning
confidence: 99%
“…Recently, a synthetic polymer polycaprolactone was successful in growing increasing numbers of stem cells from apical papilla stem cells with apparent identification of NOTCH signaling expression. [23][24][25][26] Although the number of scaffolds has increase questions remain that must be addressed.…”
Section: Scaffoldsmentioning
confidence: 99%